Assessment of Carbon Monoxide Emissions from Vehicles in Rajshahi City: Effects on Health and Environment (Journal of Environmental Science and Natural Resources, 2025)
Transport plays a crucial role in modern life, but vehicle emissions pose significant environmental and health risks. This study was conducted in Rajshahi, one of Bangladesh’s six metropolitan cities, to assess carbon monoxide (CO) emissions from the transport sector and determine human exposure levels within the city. The research involved instrumental testing of vehicle emissions using a portable Carbon Monoxide Meter (Model: AS8700A). Field observations targeted 3 cars, 3 motorcycles, 3 buses (petrol engines), and 6 trucks (both petrol and diesel engines) to measure CO levels in the surrounding environment. Results showed that CO emissions from diesel engine trucks ranged from 257 ppm to 680 ppm, while petrol engine trucks emitted 159 ppm to 570 ppm, with diesel engines producing significantly higher emissions due to their high carbon content. Petrol-powered cars emitted between 100 ppm and 310 ppm CO. Motorcycles and petrol-engine buses had CO emissions ranging from 80 ppm to 265 ppm and 175 ppm to 410 ppm, respectively. The highest CO emissions were recorded from diesel engine trucks, while motorcycles had the lowest. The recorded emission levels were notably high, likely due to the carbon content in fuels, the presence of heavy vehicles, and surrounding environmental factors. These excessive emissions contribute to environmental degradation and pose serious health risks to city residents. To mitigate these impacts, regular monitoring, stricter emission standards, and sustainable transportation policies are essential to ensure air quality and a healthier urban environment.Environ. Sci. & Natural Resources, 14(1&2): 20-26, 2025